Standard specification for Ductile Iron Castings (American Society of Testing Materials, 2009)
This specification covers castings made of ductile iron, also known as spheroidal or nodular iron, that is described as cast iron with the graphite substantially spheroidal in shape and essentially free of other forms of graphite, as defined in Terminology A 644.